Basidiomicetos resupinados de Costa Rica. Litschauerella, Subulicystidium y Tubulicium (Corticiaceae s.l.) - Kisimova-Horovitz, Liuba; Oberwinkler, Franz; Gómez P., Luis D (Revista de Biología Tropical, 1997)
Eleven species of resupinate basidiomycetes: LitsclUluerella abietis; Subulicystidium brachysporum, cochleum, longisporum, meridense, naviculatum, perlongisporum; Tubulicium dussii, vermicularis, vermiferum, rhaphidosporwn (Boid. & Gilles) Oberw., Kisimova& Gómez, comb.nov., ramonense Oberw., Kisi’;!Ova & Gómez nov. sp. (Corticiaceae s.l.) arc reported from Cost a Rica. Al! the species are briefly described and illustrated. The term"podoradix" is coined to describe therootlike processesthat anchorthe cystidiato lhe substrate. It is cxpected thatfuture, intensivc fie1dwork on these fungi wiil rcvea! the existence of many more spccies in Costa Rica, particularly in elevations abóve 1 500 m.